INTERACTIVE METADISCOURSE FEATURES USED BY TEACHERS IN BIPA ONLINE CLASSES - Shanty Duwila; Ari Astutik; Iska Agnesya Fereralda; Artika Wulandari (Leksema: Jurnal Bahasa dan Sastra, 2023)
Language features used by BIPA teachers become one of essential parts during online teaching process. This study incorporated interactive metadiscourse (IMD) proposed by Hyland (2005). It was aimed at describing the functions of the categories and understanding the ways teachers employing IMD markers in BIPA digital classes. The data sources were 4 online BIPA learning videos. Aside from employing a qualitative-descriptive method, this study also used documentation technique and content analysis for collecting and analyzing the data through the process of transcribing the video, coding the data, inputting the data in AntCont 3.4.3, selecting the target words, calculating the occurrences and average, interpreting the data, and drawing conclusion. The results of this study revealed that BIPA teachers incorporated all five categories of IMD markers. The most common IMD markers used are: ok, nah, jadi, lihat, coba, dan karena, kalau,and misalnya. The discourse markers mostly assisted the BIPA teachers to direct students, to point on the slides, to shift from one topic to another, and to express agreements.  The findings of this research are expected to give benefits theoretically for scholars and practically for BIPA teachers in conducting online learning.